Exposure of chlorothalonil and acetamiprid reduce the survival and cause multiple internal disturbances in Apis mellifera larvae reared in vitro - Lu, Ying; Gao, Jing; Wu, Tong; Han, Bo; Qian, Bingnan; Shi, Min; Yang, Sa; Diao, Qingyun; Bu, Chunya; Dai, Pingli (Frontiers in Physiology, 2023)
Background: Chlorothalonil and acetamiprid are chemical pesticides commonly used in agricultural production and have been shown to have negative effects on bee’s fitness. Despite many studies have revealed that honey bee (Apis mellifera L.) larvae are posting a high risk on exposure to pesticides, but the toxicology information of chlorothalonil and acetamiprid on bee larvae remain limited. Results: The no observed adverse effect concentration (NOAEC) of chlorothalonil and acetamiprid for honey bee larvae were 4 μg/mL and 2 μg/mL, respectively. Except for CarE, the enzymic activities of GST and P450 were not influenced by chlorothalonil at NOAEC, while chronic exposure to acetamiprid slightly increased the activities of the three tested enzymes at NOAEC. Further, the exposed larvae showed significantly higher expression of genes involved in a series of different toxicologically relevant process following, including caste development (Tor (GB44905), InR-2 (GB55425), Hr4 (GB47037), Ac3 (GB11637) and ILP-2 (GB10174)), immune system response (abaecin (GB18323), defensin-1 (GB19392), toll-X4 (GB50418)), and oxidative stress response (P450, GSH, GST, CarE). Conclusion: Our results suggest that the exposure to chlorothalonil and acetamiprid, even at concentrations below the NOAEC, showed potentially effects on bee larvae’s fitness, and more important synergistic and behavioral effects that can affect larvae fitness should be explored in the further.